1990
DOI: 10.1182/blood.v75.1.67.67
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-4 has basophilic and eosinophilic cell growth-promoting activity on cord blood cells

Abstract: Effects of human recombinant interleukin-4 (IL-4) on cord blood cells depleted of T cells and monocytes were tested in colony assays and liquid cultures. IL-4 did not induce colony formation in semisolid medium, but enhanced generation of basophil colonies induced by conditioned medium (CM) of the bladder carcinoma cell line 5637. In liquid cultures, variable degrees of basophil growth were observed in the presence of IL-3, granulocyte-macrophage colony-stimulating factor (GM-CSF), G-CSF, and 5637 CM, or even … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

1992
1992
2005
2005

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…It has been shown that CD4 + Th2 cells are present and activated in the bronchial wall and lavage fluid of atopic asthmatics ( 53 , 54 ). IL-4 and IL-5, produced by Th2 cells, have been postulated to have central roles in the initiation and maintenance of allergic inflammation because IL-4 is essential for sustaining a Th2-type immune response ( 55 ), acts on mast cells and eosinophils ( 56 ), and is a critical factor for IgE isotype switching in B cells ( 57 ). IL-5 regulates growth, differentiation, and activation of eosinophils ( 58 , 59 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that CD4 + Th2 cells are present and activated in the bronchial wall and lavage fluid of atopic asthmatics ( 53 , 54 ). IL-4 and IL-5, produced by Th2 cells, have been postulated to have central roles in the initiation and maintenance of allergic inflammation because IL-4 is essential for sustaining a Th2-type immune response ( 55 ), acts on mast cells and eosinophils ( 56 ), and is a critical factor for IgE isotype switching in B cells ( 57 ). IL-5 regulates growth, differentiation, and activation of eosinophils ( 58 , 59 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is, however, tempting to speculate that eosinophil‐derived IL‐4 may participate in an autocrine manner for enhancing the proliferative response to IL‐3 and IL‐5. 22 The important question of the effect of IL‐4 on regulation of eosinophil differentiation requires further elucidation.…”
Section: Discussionmentioning
confidence: 99%
“…Increased numbers of T cells expressing T‐helper (Th) type 2 cytokines, such as interleukin (IL)‐4 and IL‐5, have been identified in the airways of asthmatics 2,3 . Th2 cells may orchestrate asthmatic inflammation by increasing specific immunoglobulin E (IgE) levels through an action of IL‐4 on B cells and by increasing the terminal differentiation and activation of eosinophils through the release of IL‐5 4,5 . Th2 cells may modulate the development of chronic structural changes in the airways.…”
Section: Introductionmentioning
confidence: 99%